Cardiotonic steroids as potential Na+/K+-ATPase inhibitors – a computational study. (4th May 2019) - Patel, Chirag N.; Kumar, Sivakumar Prasanth; Modi, Krunal M.; Soni, Mehul N.; Modi, Nainesh R.; Pandya, Himanshu A.
Abstract: Cardiotonic steroids (CTS) are steroidal drugs, processed from the seeds and dried leaves of the genus Digitalis as well as from the skin and parotid gland of amphibians. The most commonly known CTS are ouabain, digoxin, digoxigenin and bufalin. CTS can be used for safer medication of congestive heart failure and other related conditions due to promising pharmacological and medicinal properties. Ouabain isolated from plants is widely utilized in in vitro studies to specifically block the sodium potassium (Na + /K + -ATPase) pump. For checking, whether ouabain derivatives are robust inhibitors of Na + /K + -ATPase pump, molecular docking simulation was performed between ouabain and its derivatives using YASARA software. The docking energy falls within the range of 8.470 kcal/mol to 7.234 kcal/mol, in which digoxigenin was found to be the potential ligand with the best docking energy of 8.470 kcal/mol. Furthermore, pharmacophore modeling was applied to decipher the electronic features of CTS. Molecular dynamics simulation was also employed to determine the conformational properties of Na + /K + -ATPase-ouabain and Na + /K + -ATPase-digoxigenin complexes with the plausible structural integrity through conformational ensembles for 100 ns which promoted digoxigenin as the most promising CTS for treating conditions of congestive heart failure patients.